2021
DOI: 10.1021/acs.nanolett.1c00706
|View full text |Cite
|
Sign up to set email alerts
|

Oleylamine Aging of PtNi Nanoparticles Giving Enhanced Functionality for the Oxygen Reduction Reaction

Abstract: We report a rapid solution-phase strategy to synthesize alloyed PtNi nanoparticles which demonstrate outstanding functionality for the oxygen reduction reaction (ORR). This one-pot coreduction colloidal synthesis results in a monodisperse population of single-crystal nanoparticles of rhombic dodecahedral morphology with Pt-enriched edges and compositions close to Pt 1 Ni 2 . We use nanoscale 3D compositional analysis to reveal for the first time that oleylamine (OA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…Nanostructures’s 3D morphology, in both terms of the particle size and shape, can be better studied by 3D electron tomography. A number of electrocatalysts with different morphology have been investigated, including nanoporous and nanodendrites ( Mourdikoudis et al, 2013 ; Geboes et al, 2016 ; Mourdikoudis et al, 2019 ; Pappert et al, 2019 ; Yu et al, 2019 ), nano platelets ( Kong et al, 2013 ; Toth et al, 2016 ; González-Jiménez et al, 2018 ), nanoframes and nanocages ( Becknell et al, 2017 ; Zhang et al, 2019a ; Gong, 2021a ), nanowires ( Bu et al, 2016 ; Liu et al, 2020 ), and the most widely studied nanoparticles ( Liu et al, 2012 ; Lu et al, 2014 ; Mourdikoudis et al, 2015 ; Londono-Calderon et al, 2017 ; Kang et al, 2018 ; Gong, 2021b ; Frank et al, 2021 ; Leteba et al, 2021 ).…”
Section: D Electron Tomography For Electrocatalysts At Nanoscalementioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructures’s 3D morphology, in both terms of the particle size and shape, can be better studied by 3D electron tomography. A number of electrocatalysts with different morphology have been investigated, including nanoporous and nanodendrites ( Mourdikoudis et al, 2013 ; Geboes et al, 2016 ; Mourdikoudis et al, 2019 ; Pappert et al, 2019 ; Yu et al, 2019 ), nano platelets ( Kong et al, 2013 ; Toth et al, 2016 ; González-Jiménez et al, 2018 ), nanoframes and nanocages ( Becknell et al, 2017 ; Zhang et al, 2019a ; Gong, 2021a ), nanowires ( Bu et al, 2016 ; Liu et al, 2020 ), and the most widely studied nanoparticles ( Liu et al, 2012 ; Lu et al, 2014 ; Mourdikoudis et al, 2015 ; Londono-Calderon et al, 2017 ; Kang et al, 2018 ; Gong, 2021b ; Frank et al, 2021 ; Leteba et al, 2021 ).…”
Section: D Electron Tomography For Electrocatalysts At Nanoscalementioning
confidence: 99%
“…The 3D study showed that the structure resembled a highly concave particles that nearly only skeleton remained, providing high surface area. Recently, Leteba et al reported that rhombic dodecahedral Pt-Ni nanoparticles after oleylamine aging showed enhanced ORR activity ( Leteba et al, 2021 ). By comparing the 3D morphology of Pt-Ni nanoparticles before and after aging, concave facets with exceptionally high surface area were revealed.…”
Section: D Electron Tomography For Electrocatalysts At Nanoscalementioning
confidence: 99%
“…The most successful NPs reported to date, formed by the dilution of costly Pt with less-expensive 3d-transition metals, show good catalytic performance [ 2 , 7 , 8 , 9 ], but further improvement is sought. Optimising the functionality of alloy NP electrocatalysts, particularly for the ORR, requires an understanding of the solution-phase (wet-chemical) synthetic process [ 3 , 6 , 10 , 11 ]. Solution-phase synthesis of NPs for industrial applications should ideally result in NP structures with a high degree of crystallinity, narrow particle size distribution, uniform morphology and excellent dispersability in organic solvents [ 6 , 7 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimising the functionality of alloy NP electrocatalysts, particularly for the ORR, requires an understanding of the solution-phase (wet-chemical) synthetic process [ 3 , 6 , 10 , 11 ]. Solution-phase synthesis of NPs for industrial applications should ideally result in NP structures with a high degree of crystallinity, narrow particle size distribution, uniform morphology and excellent dispersability in organic solvents [ 6 , 7 , 11 , 12 , 13 , 14 ]. However, the reduction of two or more different metal precursors in solution-based media often leads to the creation of core-shell, hetero-structured, or segregated NPs, rather than homogenous nanoalloys, due to differences in the standard reduction potentials of the metal precursors [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations have shown that Pt alloying with transition metals (Ni, Co, Fe, etc.) would be effective for creating the said nanostructures with significantly enhanced Pt activity toward ORR, due to transitional metal-induced alternations in the electronic structure of the topmost Pt atoms for weakening the adsorption of oxygenated species .…”
Section: Introductionmentioning
confidence: 99%